ANALISIS PENGGUNAAN PHOTOVOLTAIC DAN PEMBEBANAN PADA BANGUNAN USAHA MIKRO KECIL MENENGAH - Harry Miswar; A Tossin Alamsyah; Asrizal Tatang (Politeknik Negeri Jakarta, 2022)
The growth of the business world is currently growing rapidly, so the use of energy is also getting higher and the costs are not small. This study aims to carry out load analysis and PV planning towards energy efficient buildings at PT PSI. The method used in this research is survey method, documentation and literature study. Primary data is obtained from the 2020 Electricity Bill. The primary data is used to calculate the load requirement of the bending tool. The results showed that the power requirement of the bending tool was 7.4 kw/day or 59,888 kw per month with 47 PV designs with a capacity of 385 wp/unit producing 18.06 kw/day or 542 kw/month. Electrical energy savings per month is IDR 891,048 or IDR 10,692,576 per year with 47 units of 385 wp PV capacity.